Changing Patterns of Bloodstream Infections in the Community and Acute Care Across 2 Coronavirus Disease 2019 Epidemic Waves: A Retrospective Analysis Using Data Linkage. (1st October 2021) - Zhu, Nina J; Rawson, Timothy M; Mookerjee, Siddharth; Price, James R; Davies, Frances; Otter, Jonathan; Aylin, Paul; Hope, Russell; Gilchrist, Mark; Shersing, Yeeshika; Holmes, Alison
Abstract: Background: We examined community- and hospital-acquired bloodstream infections (BSIs) in coronavirus disease 2019 (COVID-19) and non–COVID-19 patients across 2 epidemic waves. Methods: We analyzed blood cultures of patients presenting to a London hospital group between January 2020 and February 2021. We reported BSI incidence, changes in sampling, case mix, healthcare capacity, and COVID-19 variants. Results: We identified 1047 BSIs from 34 044 blood cultures, including 653 (62.4%) community-acquired and 394 (37.6%) hospital-acquired. Important pattern changes were seen. Community-acquired Escherichia coli BSIs remained below prepandemic level during COVID-19 waves, but peaked following lockdown easing in May 2020, deviating from the historical trend of peaking in August. The hospital-acquired BSI rate was 100.4 per 100 000 patient-days across the pandemic, increasing to 132.3 during the first wave and 190.9 during the second, with significant increase in elective inpatients. Patients with a hospital-acquired BSI, including those without COVID-19, experienced 20.2 excess days of hospital stay and 26.7% higher mortality, higher than reported in prepandemic literature. In intensive care, the BSI rate was 421.0 per 100 000 intensive care unit patient-days during the second wave, compared to 101.3 pre–COVID-19. The BSI incidence in those infected with the severe acute respiratory syndrome coronavirus 2 Alpha variant was similar to that seen with earlier variants. Conclusions: The pandemic have impacted the patterns of community- and hospital-acquired BSIs, in COVID-19 and non–COVID-19 patients. Factors driving the patterns are complex. Infection surveillance needs to consider key aspects of pandemic response and changes in healthcare practice. Abstract : The COVID-19 pandemic has had impact on patterns of community- and hospital-acquired bloodstream infections in COVID-19 and non–COVID-19 patients. High incidence of hospital-acquired bacteremia was seen during the COVID-19 waves, particularly in SARS-CoV-2–negative elective patients.